Pengaruh Technology Readiness Index Terhadap Keinginan Untuk Menggunakan Internet Banking Pada PT Bank Mandiri KCP Pondok Chandra Surabaya - Tuwanku Aria Auliandri; Rahesti Dyah Arimbi (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2021)
This study aims to measure the degree of readiness of the individual to intention to use internet banking on PT Bank Mandiri Surabaya. Approach with Technology Readiness index, have four variables that can measure the level readiness that is Optimism, innovativeness, discomfort, and insecurity. This research is quantitative research with 100 respondents who conduct financial transaction.  The data were analyzed using structural equation model (SEM) variants based, that is Partial Least Square (PLS) with SmartPLS 2.0 program. The result of analysis found that two construct of technology readiness positive effect to intention to use internet banking that is Optimism dan Innovativeness, but the result of Innovativeness found had no impact to intention to use internet banking. While construct Discomfort dan Insecurity had negative effect to intention to use internet banking, but surprisingly construct insecurity found had impact to intention to use internet banking.